Decadally cycling soil carbon is more sensitive to warming than faster‐cycling soil carbon. (December 2015) - Lin, Junjie; Zhu, Biao; Cheng, Weixin
Abstract: The response of soil organic carbon (SOC) pools to globally rising surface temperature crucially determines the feedback between climate change and the global carbon cycle. However, there is a lack of studies investigating the temperature sensitivity of decomposition for decadally cycling SOC which is the main component of total soil carbon stock and the most relevant to global change. We tackled this issue using two decadally 13 C‐labeled soils and a much improved measuring system in a long‐term incubation experiment. Results indicated that the temperature sensitivity of decomposition for decadally cycling SOC (>23 years in one soil and >55 years in the other soil) was significantly greater than that for faster‐cycling SOC (<23 or 55 years) or for the entire SOC stock. Moreover, decadally cycling SOC contributed substantially (35–59%) to the total CO2 loss during the 360‐day incubation. Overall, these results indicate that the decomposition of decadally cycling SOC is highly sensitive to temperature change, which will likely make this large SOC stock vulnerable to loss by global warming in the 21st century and beyond.